Pendampingan Pembelajaran Bahasa Inggris Dasar Pada Santri Pondok Pesantren Nurul Huda (PPNH) Sukaraja - Eka Warohma (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
This Accompaintement began when it was felt the importance of learning English in this eraEnglish is an international language which is used as the world's language of communication. Apart from being in the school environment, learning English is also important to be taught in non-formal education, especially in dormitories / pesantren. This community service activity aims to provide basic English learning assistance to students of PPNH Sukaraja. This training is conducted in several PPNH dormitory units such as the Central Women's Dormitory which lasts 30 minutes with meetings 2 times a week. The obstacles faced in the activity are relatively short time. But in general this activity went well and received a good reception from the students, as well as from the PPNH Sukaraja